El poder blando de China en el 2011. - Cejas Armas, Ismael (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
Soft power is a Joseph Nye's concept to describe world powers' international soft behaviors in an aggressive environment where traditionally power is the unique mean. Formulated to change some immediate international American politics, has been China who has became the major sponsor of the idea in foreign aff airs. Th is essays tries to make an explanation and a balance of such politics in 2011 to understand its consequences for all the international actors involved with the new world power.